Synthesis, isomerization and biological activity of novel 2-selenohydantoin derivatives. Issue 4 (15th February 2016) - Ivanenkov, Yan A.; Veselov, Mark S.; Rezekin, Igor G.; Skvortsov, Dmitriy A.; Sandulenko, Yuri B.; Polyakova, Marina V.; Bezrukov, Dmitry S.; Vasilevsky, Sergey V.; Kukushkin, Maxim E.; Moiseeva, Anna A.; Finko, Alexander V.; Koteliansky, Victor E.; et al.
Graphical abstract: Abstract: A set of novel selenohydantoins were synthesized via a convenient and versatile approach involving the reaction of isoselenocyanates with various amines. We also revealed an unexpected Z → E isomerization of pyridin-2-yl-substituted selenohydantoins in the presence of Cu 2+ cations. The detailed mechanism of this transformation was suggested on the basis of quantum-chemical calculations, and the key role of Cu 2+ was elucidated. The obtained compounds were subsequently evaluated against a panel of different cancer cell lines. As a result, several molecules were identified as promising micromolar hits with good selectivity index. Instead of analogous thiohydantoins, which have been synthesized previously, selenohydantoins demonstrated a relatively high antioxidant activity comparable (or greater) to the reference molecule, Ebselen, a clinically approved drug candidate. The most active compounds have been selected for further biological trials.